ANALISIS PENGARUH VARIABEL MAKRO TERHADAP PERMINTAAN REKSA DANA SAHAM DI INDONESIA PERIODE 2001 - 2011 - Akmal Umar; Nur Vadila Putri (Media Riset Bisnis & Manajemen, 2013)
The purpose of this study is to analyze how macroeconomics variables, such as interest rate (BI rate), inflation, exchange rate rupiah, GDP per capita and the money supply, influence the demands of equity funds in Indonesia. This study use time series data from 2001 through 2011quarter by using multiple linear regression model and Ordinary Least Square (OLS) method. The result of this study indicates that Net Asset Value of equity funds in Indonesia has increased in 2002 — 2004 in the period of the study. It is influenced by 4 strong macroeconomics indicators in Indonesia along with the improving economic of the country. Downward trends of interest rate happened in early 2002 until 2005 has encouraged investors to search another alternative investment instrument, so that the demands of equity funds increased.